2020
DOI: 10.3390/su12124962
|View full text |Cite
|
Sign up to set email alerts
|

The Links between Proactive Environmental Strategy, Competitive Advantages and Firm Performance: An Empirical Study in Vietnam

Abstract: The acceleration of environmental problems has put firms under high pressure to assume their social and environmental responsibility. This study aims to investigate the links between proactive environmental strategy, competitive advantages and firm performance. It also explores the control effects of firm size and industry type on the adoption of such a strategy. Data were obtained from 232 firms that participated in the program on benchmarking and announcing sustainable companies in Vietnam. Findings from str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 105 publications
(162 reference statements)
9
73
2
3
Order By: Relevance
“…The existing studies focus on the influencing factors of enterprise environmental protection investment [ 21 , 36 , 37 , 39 ] or the economic consequences [ 40 , 41 , 42 , 43 ] and do not use an intermediary variable for internal control capabilities to indirectly affect financial performance. Based on the perspective of resource-based perspective, this article regards corporate environmental protection investment activities as an important resource that is scarce, valuable, and difficult to replicate [ 44 , 45 ], which can positively affect corporate financial performance and effectively explain the motivation for companies to actively invest in environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…The existing studies focus on the influencing factors of enterprise environmental protection investment [ 21 , 36 , 37 , 39 ] or the economic consequences [ 40 , 41 , 42 , 43 ] and do not use an intermediary variable for internal control capabilities to indirectly affect financial performance. Based on the perspective of resource-based perspective, this article regards corporate environmental protection investment activities as an important resource that is scarce, valuable, and difficult to replicate [ 44 , 45 ], which can positively affect corporate financial performance and effectively explain the motivation for companies to actively invest in environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, current research outcomes demonstrated that the association is not direct between companies' performance and execution of volunteer eco-friendly exercises [2,31,32]. According to Do and Nguyen [33], Hoang et al [34], and Cheng et al [35], the association between environmental strategies and companies' performance is meditated through some prominent factors. Thus, the reinvestigation of this association has become very vital.…”
Section: Introductionmentioning
confidence: 83%
“…The co-evolutionary and neoclassical techniques from evolutionary theory on innovation [16,43] and innovation economics to environmental economics [44] have demonstrated eco-innovation. According to Do and Nguyen [33] and Rehfeld et al [45], several studies have used general innovation theory to explain eco-innovation, and it was further extended to become the environmental innovation theory [46]. Afterwards, several researchers have used this approach [47].…”
Section: Theory Underpinning-resource-based View Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This research proposes a multi-level growth curve model (MGCM) to examine how multi-level CSR results in more growth of multi-level GOI, which in turn leads to more growth in PES adoption at the individual level. Indeed, past studies have begun to investigate environmental performance through the implementation of a PES [16], but few studies have focused on the driving factors of adopting a PES for company-level variables (e.g., CSR at the work unit level), which has caused a gap in the literature.…”
Section: Research Gapsmentioning
confidence: 99%